Consecuencias jurídicas de la eliminación de la tabla de tenencia y consumo de drogas y su afectación al consumidor en la forma de administrar justicia. - Mullo Anilema Víctor Hugo (2025)
The subject to be studied is the legal consequences of the elimination of the table of possession and consumption of drugs and its impact on the consumer in the way of administering justice, after the repeal of Resolution No. 001Consep-CD-2013 is one of the topics that is lately under discussion in different parts of Ecuador, as well as at an international level. In the Constitution of the Republic of Ecuador in its article 364 in accordance with article 220 of the Comprehensive Organic Penal Code regulated and differentiated between consumers and sellers of substances that are subject to control, in this way judges could identify and distinguish each individual in order to sanction correctly. The objective of the study is to analyze the legal consequences of the elimination of the table of possession and consumption of drugs and its impact on the consumer in the way of administering justice, for this a mixed methodology will be used, between the qualitative and quantitative method; in the same way the methods used are inductive - deductive. The technique that will be used for the development of this research work is the bibliographic review and surveys. As results, it is intended to obtain a legal study that incorporates normative and theoretical foundations on the elimination of the table of consumption and possession of drugs regarding the legal vacuum that this has caused and the problem that it has generated for consumers in the way of administering justice. Keywords: elimination, table, consumption, sale, drugs.